2007
DOI: 10.1007/978-3-540-74796-3_55
|View full text |Cite
|
Sign up to set email alerts
|

Towards Applicable 3D User Interfaces for Everyday Working Environments

Abstract: Abstract. Desktop environments represent a powerful user interface and have been used as the de facto standard human-computer interaction paradigm for over 20 years. But the rising demand of 3D applications dealing with complex datasets exceeds the capabilities of traditional interaction devices and two-dimensional displays. Such applications need more immersive and intuitive interfaces. In order to be accepted by the users, technology-driven solutions that require inconvenient instrumentation, e.g., stereo gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Based on the above preconditions, we designed an algorithm based on a combination of Steer-to-Center (S2C) [15,50] and Steer-to-Action (S2A) [43]. S2C is one of the most basic generalized algorithms, and it determines the curvature and/or rotation gain of redirection so that the user's walking direction is toward the center of the play area.…”
Section: User-steering Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above preconditions, we designed an algorithm based on a combination of Steer-to-Center (S2C) [15,50] and Steer-to-Action (S2A) [43]. S2C is one of the most basic generalized algorithms, and it determines the curvature and/or rotation gain of redirection so that the user's walking direction is toward the center of the play area.…”
Section: User-steering Algorithmmentioning
confidence: 99%
“…Specifically, to provide haptic feedback during door opening at arbitrary positions in VR, we implemented a small number of wheeled robots (called door robots) equipped with a doorknob-like haptic prop and a robot-positioning algorithm to position them at proper timing while avoiding collisions. In addition, to guide the user away from the boundary of the physical play area, we designed and implemented a user-steering algorithm, based on existing algorithms [15,43,50], that adaptively determines the redirection gain for every instance of door opening. To evaluate the performance of RDD+, we first conducted a simulation study to investigate the effects of VE type, user walking speed, and number of door robots on the spatial efficiency of redirection and robot placement delay.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Bornik et al (2006) showed an interface for volumetric medical data combining a tablet PC with a stereoscopic projection and using a custom handheld input device for both modalities. Steinicke et al (2007) published a 3D interaction framework for everyday working environments, again using an autostereoscopic monitor with spatial and conventional input combined. Lately, Reipschläger and Dachselt (2019) extended an 2D interactive touch and stylus activated display with AR capabilities.…”
Section: Related Researchmentioning
confidence: 99%